Skills development through an Alumni and student mentoring programme: A collaborative approach - Rossiter, Isabel; Gardiner, Glynis (ICAReAlumni Conference Proceedings, 2019)
The aim of this voluntary, extra-curricular mentoring programme is to provide guidance and support to students, as well as enhance their personal and professional skills, and further develop industry knowledge. Alumni give their time as Mentors to impart their knowledge, expertise and business experience to guide students in their transition from higher education in to the working world.